Assessment of immunogenicity and efficacy of a Zika vaccine using modified vaccinia Ankara virus as carriers - López-Camacho, C; Kim, Y; Abbink, P; Larocca, R; Huiskonen, J; Barouch, D; Reyes-Sandoval, A (MDPI, 2019)
Zika virus (ZIKV) is an emerging mosquito-borne flavivirus that has spread to more than 70 countries worldwide since 2015. Despite active research, there are currently no licensed vaccines or therapeutics. We have previously reported the development of various adenoviral vectored vaccine candidates (ChAdOx1 ZIKV) with the ability to stimulate effective immunity in mice and provide protection upon a ZIKV challenge model, using a non-adjuvanted single vaccination approach. In this study, we constructed various modified vaccinia Ankara (MVA) viruses to express the ZIKV Envelope (E) with modifications on the precursor membrane (prM) or on the C-terminus envelope transmembrane domain (TM), similar to our ChAdOx1 vaccine candidates. MVA-ZIKV vaccine candidates were evaluated as a non-adjuvanted single vaccination regimen against a ZIKV Brazilian isolate, using viraemia as the correlate of protection. Here, we report the induction of a modest level of anti-ZIKV E antibodies by all MVA vectored vaccines and sub-optimal efficacy in a ZIKV challenge model. Our results indicate the requirement of additional strategies when using MVA-ZIKV vaccines to afford sterile protection upon a non-adjuvanted and single vaccination regime.